2016
DOI: 10.1308/rcsann.2016.0163
|View full text |Cite
|
Sign up to set email alerts
|

The impact of The Royal College of Surgeons of England research fellowship scheme

Abstract: Introduction The research fellowship scheme for surgeons in training run by The Royal College of Surgeons of England (RCS) had its 20th anniversary in 2013. A survey was undertaken to assess outcomes of the scheme during those 20 years. Methods Fellowship recipients were invited to complete an online 20-item questionnaire about their fellowship research and research activities since its completion. The questionnaire covered type of research undertaken, higher research degree enrolment, publications resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The impact of a research fellowship on subsequent publications has been shown previously by The Royal College of Surgeons of England and others. 5,6 On the other hand, in the study of Agarwal et al, the h-index did not differ between fellowship-and non-fellowship-trained practitioners. 7 Obviously, it was no coincidence to find both of these findings in our study population, since academic status significantly contributes to the advancement of a physician in our institute.…”
Section: Discussionmentioning
confidence: 75%
“…The impact of a research fellowship on subsequent publications has been shown previously by The Royal College of Surgeons of England and others. 5,6 On the other hand, in the study of Agarwal et al, the h-index did not differ between fellowship-and non-fellowship-trained practitioners. 7 Obviously, it was no coincidence to find both of these findings in our study population, since academic status significantly contributes to the advancement of a physician in our institute.…”
Section: Discussionmentioning
confidence: 75%
“…Due to the methodology used and information gathered in the present study, it is difficult to compare with other key studies exploring benefits and outcomes from scholarships. However, one clear common outcome is that receiving a scholarship or grant increases publication rates and future funding opportunities for recipients, 4,5,9,10 with many progressing in academic profile 10 …”
Section: Discussionmentioning
confidence: 99%
“…4,7 Due to the methodology used and information gathered in the present study, it is difficult to compare with other key studies exploring benefits and outcomes from scholarships. However, one clear common outcome is that receiving a scholarship or grant increases publication rates and future funding opportunities for recipients, 4,5,9,10 with many progressing in academic profile. 10 Discrepancies in search results from Scopus, Google Scholar, PubMed and ResearchGate have previously been reported, [11][12][13] consistent with discrepancies between different databases presented here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations